One-step hydroxylation of benzene to phenol via a Pd capillary membrane microreactor - Wang, X.; Tan, X.; Meng, B.; Zhang, X.; Liang, Q.; Pan, H.; Liu, Shaomin (R S C Publications, 2013)
A novel Pd capillary membrane microreactor for one-step hydroxylation of benzene to phenol was synthesized and investigated to showcase the effectiveness of ‘Niwa concept’. Reaction parameters including H2/O2 ratio and temperature were systematically studied for their effects on benzene conversion and phenol yield. A detailed examination of different membrane reactors, feed mode and long-term reaction stability was also conducted. Pd capillary membrane displayed good stability for low temperature separation and reaction due to the excellent anchorage of Pd layer into the porous α-alumina support. An optimum H2/O2 ratio was identified at 473 K with the benzene conversion of 19.6% and phenol yield of 18.1%. An increase in reaction temperature caused not only an increase in benzene conversion but also a decrease in phenol selectivity. A comparison between our work and the literature results was also made to discuss the feasibility of the membrane reactor concept. Experimental results proved that narrow flow channels and larger Pd membrane surface area-to-volume ratios provided more effective area of Pd interface and promoted the radial diffusion of reactants, enabling the reactive species more opportunities to react directly with benzene resulting in high benzene conversion.